Eksistensi Awik-Awik Sebagai Legalitas Pernikahan Dini di Pulau Lombok - Yuslih, Muhammad (Pusat Studi Gender dan Anak Universitas Islam Negeri Antasari Banjarmasin, 2023)
The value of local wisdom in the Sasak community on the island of Lombok has shifted away from the awik-awik tradition. This shift is believed to have contributed to the high rate of early marriage. The researcher aims to investigate whether the awik-awik tradition is the cause of early marriage practices, using Anthony Giddens' theory of legal awareness and structuration as a framework. This qualitative research employs interview and documentation methods to gather data. The study's findings suggest that the awareness of the law of 'awik-awik' among the Sasak people, particularly minors, is very low. This is supported by the number of young people who intentionally violate 'awik-awik' by getting married without their parents' permission or blessing. Furthermore, there is a close relationship between the perpetrators of early marriage (agents) and the structure of this violation of 'awik-awik'. Agents are under the authority of community and religious leaders, such as the dusun head, RT, and penghulu. If someone violates the awik-awik, these leaders are the first to take action. Violating the awik-awik is considered a disgrace, especially for minors, who may be forced into marriage as a result. It is important to note that minors who violate the awik-awik have no choice but to marry, as this is a legitimate sanction according to the awik-awik.